Comparison between Folin‐Ciocalteu and Prussian Blue Assays to Estimate The Total Phenolic Content of Juices and Teas Using 96‐Well Microplates. Issue 11 (8th October 2015) - Margraf, Tiago; Karnopp, Ariadne Roberto; Rosso, Neiva Deliberali; Granato, Daniel
Abstract: Folin‐Ciocalteu colorimetric assay (FC) is the most widely used assay to estimate the total phenolic content in foods, beverages, herbs and other plant extracts, but many chemical compounds may act as interfering agents, producing inaccurate estimations of the real concentration of phenolic compounds in the matrix. Based on this limitation, the objective of this study was to compare, quantitatively, the Folin‐Ciocalteu and Prussian Blue (PB) assays in estimating the total phenolic content in purple grape juices ( n = 20; Vitis labrusca L.) and teas ( n = 25) from different botanical origins using 96‐well microplates. PB assay presented a low limit of detection (PB = 0.27 mg/L; FC = 0.25 mg/L) and quantification (PB = 0.92 mg/L; FC = 0.82 mg/L), showing its suitability in screening the total phenolic content in grape juices and teas. FC and PB assays presented a high association ( P < 0.0001) for teas ( r = 0.887) and grape juices (r = 0.923). The advantages of PB over FC assay are its simplicity, low time consumption (15 min reaction as compared to 60 min reaction for the FC assay), lower usage of reagents (solutions are prepared in a mM base), and higher selectivity. Additionally, PB assay was proven to be reproducible and repeatable and, therefore, may be used as an alternative to FC assay.